The effects of acute versus chronic sodium bicarbonate supplementation on high-intensity intermittent sprint performance in rugby union players - Fitzpatrick, P.; Warrington, G. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Exogenous ingestion of alkalising agents, such as sodium bicarbonate (SB), has been shown to enhance muscle buffering capacity, thereby delaying the metabolic acidosis associated with high-intensity exercise and potentially improving performance. The aim of this research was to examine the effects of acute and chronic SB supplementation in comparison to a placebo (PLA) on high-intensity intermittent sprint performance in trained rugby union players. Methods: Using a double-blind, randomised, cross-over design, ten trained male rugby union players (age 28 ± 5 years) completed four separate trials - two acute and two chronic supplementation trials. For the acute trials, subjects ingested either 0.3g/kg body mass (BM) of NaHCO3 (SB-A) or a placebo (PLA-A) separated into three equal doses at 90, 60 and 30 minutes prior to the performance test. Chronic supplementation consisted of ingesting 0.3g/kg BM of NaHCO3 (SB-C) or a placebo (PLA-C) each day for five consecutive days prior to the performance test. Using a resistance of 7.5% body mass, the performance test protocol consisted of 6 x 10s maximal sprints on a cycle ergometer followed by 50 seconds active recovery prior to each subsequent sprint. Peak power output (PPO) and mean power output (MPO) were recorded for each 10s sprint. Blood bicarbonate (StdHCO3-), pH, base excess (BE-Ecf), blood lactate, PCO2 and PO2 were also measured. Results: Acute SB supplementation demonstrated significant elevations in pre-exercise levels for blood bicarbonate (StdHCO3-), pH and base excess (BE-Ecf) but no significant improvement in peak power output (PPO), mean power output (MPO) or total work (TW). Chronic SB supplementation exhibited a significant increase in StdHCO3- following Sprint 1 only. However, no significant differences in performance parameters were recorded for either acute or chronic SB supplementation when compared to the PLA trial. Discussion: The major findings of this work suggest that pre-exercise metabolic alkalosis may be induced following acute but not chronic SB ingestion. However, results are inconclusive regarding the efficacy of acute or chronic SB ingestion to enhance performance in high intensity, intermittent performance indicative of the physiological demands associated with rugby union. Results: also appear to indicate a high degree of individual variability, which, in part, may be due to potential gastrointestinal side effects of SB ingestion. Conclusion Neither acute nor chronic SB supplementation had a significant impact on performance as measured by power output in a high-intensity intermittent sprint test. Although metabolic alkalosis was induced with acute SB ingestion, identified by increases in blood StdHCO3-, pH and BE-Ecf, no ergogenic benefit was observed. The highly individual response elicited by SB supplementation warrants further research to examine the efficacy of acute and chronic SB supplementation on highintensity intermittent exercise.